2021
DOI: 10.31703/gmcr.2021(vi-i).08
|View full text |Cite
|
Sign up to set email alerts
|

Newspapers in Peril: Rationalizing the Economic Challenges of Novel Coronavirus (Covid-19) upon Regional Journalists in Hyderabad, Sindh, Pakistan

Abstract: Mass media play a decisive role in distributing health knowledge and awareness about health diseases. Covid-19 has been measured as the most dangerous health hazard of the 21st century that has constituted social, environmental and financial perils for humanity, including the media outlets. However, the Pakistani newspaper industry was already witnessing a decline in its readership and coronavirus has further deteriorated the situation for journalists working in regional newspapers. The methodological design u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Such studies have therefore suggested 'prompt action on the part of appropriate bodies to amend relevant codes of ethics' (Kamboh & Ittefaq, 2019: 2). They also demand necessary actions to establish collaboration between the government and owners of economically weak newspapers, 'to consider financial challenges encountered by journalists for the survival of the newspaper industry in Pakistan' (Nizamani et al, 2020), notably also in the context of COVID-related predicaments (Shah et al, 2021).…”
Section: Areas Of Improvement and Bottlenecks Of Development And Sciencementioning
confidence: 99%
“…Such studies have therefore suggested 'prompt action on the part of appropriate bodies to amend relevant codes of ethics' (Kamboh & Ittefaq, 2019: 2). They also demand necessary actions to establish collaboration between the government and owners of economically weak newspapers, 'to consider financial challenges encountered by journalists for the survival of the newspaper industry in Pakistan' (Nizamani et al, 2020), notably also in the context of COVID-related predicaments (Shah et al, 2021).…”
Section: Areas Of Improvement and Bottlenecks Of Development And Sciencementioning
confidence: 99%